Aktivitas di Sekolah Diliburkan saat Pendemi Covid-19: Bagaimana Pembelajaran yang Dilakukan? - Sukma Wijayanto; Dita Febri Handani; Aditia Eska Wardana; Kun Hisnan Hajron (Jurnal Bidang Pendidikan Dasar, 2020)
Abstract. This study aims to describe the learning activities carried out at Cacaban 6 Elementary School in Magelang City during the Covid-19 pandemic. This study uses a qualitative descriptive approach to obtain information from informants in learning activities. The informants in the study were the teachers taken as a sample of six people and a school principal. The results obtained from this study indicate that learning activities are carried out in two ways, namely online via the Whatsapp application, Youtube, and Google form and offline or face to face. The findings of this study reinforce the implementation of learning activities policy that must be carried out by utilizing technology during the Covid-19 pandemic. It also strengthens the participation of parents to continue to be involved in the learning process of students, thus requiring them to always be communicative. The findings of this study can be a basis for following up on the policy of learning activities from home and efforts to solve the problem. In addition, this research can be the basis for conducting further studies in relation to learning activities during the pandemic. Abstrak. Penelitian ini bertujuan mendeskripsikan pembelajaran yang dilakukan dalam pandemi Covid-19 di SD Negeri Cacaban 6 Kota Magelang. Penelitian menggunakan pendekatan deskriptif kualitatif untuk mendapatkan informasi dalam kegiatan pembelajaran. Informan dalam penelitian sebanyak 6 guru dan kepala sekolah. Hasil yang didapatkan bahwa pembelajaran dilakukan secara daring (wa, youtube, dan google form) dan luring. Temuan penelitian ini menguatkan pelaksanaan pembelajaran pada masa aktivitas libur pandemi covid 19 dalam memanfaatkan teknologi dan mengatasi keterbatasan seperti kurangnya keterlibatan orang tua dalam pembelajaran serta keterbatasan fasilitas serta harus komunikatif dengan orang tua.Temuan penelitian ini dapat menjadi landasan untuk tindak lanjut dalam pembelajaran, dan upaya-upaya pemecahan masalah. Disamping itu penelitian ini dapat menjadi landasan untuk melakukan kajian lebih dalam dalam hubungannya dengan pembelajaran yang dilakukan saat pendemi.